E-book Integrated Video Tutoring with Symbolic Modelling Techniques to Increase the Self-control of Bullying Perpetrators - Aulia, Dea; Firman (Bisma The Journal of Counseling, 2024)
Bullying has become a worrying global issue with increasing prevalence in various countries. Bullying is increasing in the world, one of which is due to lack of self-control. Group guidance using information technology such as video media is rarely implemented. The aim of this research is to develop a video-integrated group guidance E-book with symbolic modelling techniques to increase the self-control of bullies, using R & D research with the ADDIE model which includes the analysis, design, development, implementation and evaluation stages. The research sample involved 20 perpetrators of bullying. The research results revealed that (1) E-book integrated video group guidance with symbolic modelling techniques was considered very suitable for use by guidance and counseling teachers (2) Video integrated group guidance with symbolic modelling techniques was effective in increasing the self-control of bullies. The experimental group showed a much higher change in self-control scores for bullies than the control group (U= 10,000, Z= -3025, p<0.05).  These findings explain that E-book group guidance integrated with video with symbolic modelling techniques can be an alternative for increasing the self-control of students who are bullies at school.